Faktor-Faktor yang Berhubungan dengan Risiko Gagal Tumbuh Pada Anak Usia > 6-24 Bulan di Puskesmas Kenali Besar Kota Jambi Tahun 2016 - Taty Nurti; Lia Artika Sari; Ika Murtiyarini (Universitas Batanghari Jambi, 2020)
The number of toddlers in Indonesia is very large which is 10 percent of the entire population. Malnultrisi is still behind the disease and death of a child, although it still often goes unnoticed. Early detection of growth irregularities by measuring weight loss against height aimed at determining the nutritional status of children, Jambi City itself still has children who were malnourished as many as 5 people in 2015. Quantitative research with cross sectional design. The population is a mother who has children aged 6 -24 months who are in the area of Puskesmas Kenali Besar Jambi City. The sample formula uses a Rule of Thumb with corrections and amounts to 80. Quota sample sampling technique. The results of the analysis found a knowledge relationship with the risk of failing to grow in children aged 6-24 months p-Value = 0.011 (p > 0.05). There is an exclusive breastfeeding relationship with the risk of failing to grow in children aged <6-24 p-Value = 0.011 (p < 0.05). there is no family support relationship with the risk of failing to grow in children aged 6-24 months p-Value = 0.428 (p > 0.05) in the Working Area of Puskesmas Know Besar Jambi City Year 2016. For puskesmas to be able to immediately report if there has been a risk of failing to grow in the child, so that it can be addressed quickly so that the risk of failing to grow does not occur in the child.